Pengaruh Kepemimpinan Transformasional Dan Pelatihan Terhadap Kinerja Pegawai: Studi Pada Dinas Sosial Kabupaten Pamekasan - Lailatul Muizzah; Nugroho Mardi; Chamariyah Chamariyah (Universitas 45 Surabaya, 2024)
The results of the study show that: 1.) Transformational leadership has a positive and insignificant effect on employee performance with an original sample value of 0.091. 2.) Training has a significant positive effect on employee performance with an original sample value of 0.480.